Smoking and Depression Risk Reduction in a Primary Care Setting - Naveen Mahmood; Shira Goldstein; Alan Thiele; Mark Trotchie; Jude des Bordes (Journal of Primary Care & Community Health, 2023)
Introduction: Smoking is associated with many diseases and is a target for primary preventive efforts in numerous morbidities. Studies show that smoking and depression may be associated. Never-smokers are at significantly lower risk than current and former smokers. Despite this observation, the effect of smoking on depression risk reduction has not been adequately explored. The purpose of this study was to explore the effect of smoking on depression risk reduction in adult patients seen in a primary care clinic at an academic medical center 6 months after they were identified as being at risk for depression. Findings may influence the direction and intensity of our smoking cessation endeavors in patients at risk of depression who smoke. Methods: We conducted an analytic cross-sectional study using electronic medical records of patients 18 years and older seen a primary care setting between January 1, 2019 and December 31, 2020. All participants included had an initial depression risk score (assessed by the 9-item Patient Health Questionnaire (PHQ-9)) of 5 or higher, information on smoking status and a PHQ-9 score at 6 months. We determined the percentage of patients with PHQ-9 score decrease of 5 or more at 6 months and used logistic regression to determine the association depression risk reduction (of 5 units or more) at 6 months and smoking, adjusting for demographic, clinical, and behavioral characteristics. Results: Number of patients included were 120, mean age was 55 (16), years, 88 (74%) were female, 68 (57%) were African American, and 31 (26%) were Caucasian. Fifty (44%) had a history of smoking and 31 (25.8%) had improvement (ie, a decrease of 5 units or more) in their PHQ-9 score at 6 months. Smoking was associated with decreased odds of improvement in depressive symptoms (Odds ratio = 0.32, 95% Confidence interval: 0.12-0.87). Conclusion: Risk of depression was more likely to persist in smokers than non-smokers at 6 months. Addressing smoking behavior in those with risk of depression may be beneficial.